An improved consensus genetic linkage map of cowpea ( Vigna unguiculata L. Walp. ) - Diop, N.N.; Ehlers, J.D.; Wanamaker, S.; Muchero, W.; Fatokun, C.A.; Guojing, L.; Roberts, P.A.; Close, T.J.; Timothy (2012)
Consensus genetic linkage maps are formed from merging individual linkage maps. They provide powerful tools for genetic analysis and a foundation for marker-assisted breeding, trait mapping, and positional cloning. In 2009, the first cowpea consensus map was developed. It included 928 markers spanning 11 linkage groups over a total map size of 680 centimorgans (cM), a 0.73 cM average marker distance. The map was the result of merging maps from 6 RIL populations genotyped with a 1536-SNP multiplexed assay developed from EST-derived genic SNPs. Here we report improvements to the consensus map for cowpea that result from merging genotype data from a total of 1070 lines composed of eight RIL and two F4 breeding populations. Individual maps were first constructed and then merged to develop a consensus map. The improved map is 680 cM in length and contains 1043 markers, which is an addition of 115 markers and an average 0.65 cm between markers. The map resolution is also increased with more marker bins, and there were some adjustments to marker order. The current SNP-based cowpea linkage map is included in a publicly available browser called HarvEST:Cowpea, which can be downloaded as a Windows software from http://harvest.ucr.edu or viewed through an online portal www.harvest-web.org.